Effects of Iron Injection Timing on Suckling and Subsequent Nursery and Growing-Finishing Performance and Hematological Criteria under Commercial Conditions - H. E Williams; B. Carrender; R. Maurer; J. M. DeRouchey; J. C. Woodworth; S. S. Dritz; M. D. Tokach; R. D. Goodband; A. J. Holtcamp; K. F. Coble (Kansas Agricultural Experiment Station Research Reports, 2020)
A total of 1,892 newborn pigs (PIC 359 × C40; initially 3.3 lb body weight [BW]) within 172 litters were used in a 168-d study to evaluate the effects of Fe injection timing after birth on suckling and subsequent nursery and growing-finishing growth performance and hematological criteria. One day after birth, piglets were weighed, and 11 pigs within each litter were allotted to 1 of 6 treatments consisting of no Fe injection or 200 mg of injectable Fe provided on d 1, 3, 5, or 7 of age, or 200-mg on d 1 plus 200-mg on d 12 of age. Piglets were weighed individually and bled at weaning (19 d of age) to determine blood Fe status and lactation growth performance. Pigs were weaned and placed in a commercial wean-to-finish facility in a total of 15 pens with equal representation of treatments in each pen. Pigs were individually weighed on d 72 and 168 after birth to determine subsequent nursery and growing-finishing average daily gain (ADG). During the lactation phase, marginal significance for a decrease (linear;P =0.080) in preweaning ADG was observed with increasing the age at which pigs received a 200-mg Fe injection; however, there was no evidence for a difference (P>0.10) in d 19 BW. The absence of an Fe injection decreased (P= 0.0001) preweaning ADG and d 19 BW compared to pigs receiving an Fe injection. Providing a 200-mg Fe injection on d 1 plus d 12 of age showed no evidence of a difference (P>0.10) in preweaning ADG or d 19 BW compared to pigs receiving a 200-mg Fe injection on d 1 only. During the nursery (d 19 to 72 d of age) or finishing (d 72 to 168) phases, increasing the age at which pigs received a 200-mg Fe injection after birth provided no evidence for a difference (P>0.10) in subsequent nursery or finishing ADG. The absence of an Fe injection post-farrowing decreased (P= 0.0001) subsequent nursery ADG and ending BW on d 72. Overall (d 1 to 168 d of age), increasing the age at which pigs received a 200-mg Fe injection provided no evidence for a difference (P>0.10) in overall ADG. The absence of an Fe injection post-farrowing decreased (P =0.0001) overall ADG. Providing a 200-mg Fe injection on d 1 plus d 12 of age showed no evidence of a difference (P>0.10) in overall ADG compared to pigs receiving a 200-mg Fe injection on d 1 of age only. Furthermore, there was no evidence (P>0.10) that Fe injection treatments influenced preweaning or wean-to-finish mortality. The absence of an Fe injection post-farrowing provided no evidence for a difference (P>0.10) in preweaning or wean-to-finish mortality. For hematological criteria, increasing the age at which pigs received an Fe injection decreased (linear:P<0.05) hemoglobin (Hb) and hematocrit (Hct) values at d 19 of age. The absence of an Fe injection post-farrowing decreased (P= 0.0001) Hb and Hct values at d 19 of age compared to pigs receiving an Fe injection after birth. Providing a 200-mg Fe injection on d 1 plus d 12 of age increased (P= 0.0001) Hb and Hct values at weaning compared to pigs receiving a 200-mg Fe injection on d 1 only. In summary, this study provides evidence that administering 200 mg of Fe from gleptoferron within 7 d after birth optimizes preweaning and subsequent nursery and grow-finishing growth performance. Not administering 200 mg of Fe after birth significantly reduces preweaning and subsequent growth performance and blood Fe status at weaning compared to pigs receiving a 200-mg Fe injection, regardless of timing after birth.
Keywords: Gleptoferron; growth performance; hemoglobin; iron; pig; timing